Photodynamic therapy: a distinct therapeutic modality - Alla, Rama Krishna; Sarangi, SwatiSwagantika; Ganta, Gopala Krishna; Abusua, Fatima (International Journal of Dental Materials, 2023)
Photodynamic therapy (PDT) is an innovative treatment modality that utilizes a combination of a photosensitizing agent, specific wavelengths of light, and molecular oxygen to selectively target and destroy abnormal cells or tissues while sparing healthy surrounding structures. This approach has gained significant attention in the medical field due to its potential to provide effective and less invasive treatment options for various conditions. The development of PDT was driven by the need for treatments that overcome the limitations of conventional modalities such as surgery, radiation therapy, and chemotherapy. PDT offers several benefits over these approaches, including its ability to provide targeted therapy, reduced side effects, minimal damage to healthy tissues, and versatility in treating different diseases. One of the key advantages of PDT is its selectivity. By utilizing photosensitizers that accumulate in diseased or abnormal cells, PDT can precisely target the affected tissue while minimizing damage to healthy tissues. This selectivity allows for focused treatment, reducing the potential for unnecessary harm to surrounding structures. Furthermore, PDT offers faster recovery times and potentially better cosmetic outcomes compared to surgery, as it does not require extensive incisions or removal of tissues. Additionally, the localized nature of PDT minimizes systemic toxicity and long-term complications, making it a well-tolerated treatment option. PDT has demonstrated efficacy in various medical fields, including oncology, dermatology, and ophthalmology. It has been used to treat different types of cancers, including skin, lung, oesophagal, and bladder cancer, as well as manage conditions like age-related macular degeneration and certain dermatological disorders. This article reviewed the development, mechanism, and applications of PDT in the medical field.